Potensial opini masyarakat dalam konten sosial media menimbulkan hesitency terhadap vaksin COVID 19 : A Literature Review - Yessy Fitriani; Yoslien Soepamena (Dian Nuswantoro Semarang, 2022)
ABSTRACT Background and objective: Vaccine hesitency is a sign that the public is late in accepting or refusing the COVID 19 vaccine. Misinformation or hoax news on social media can reduce public trust in the COVID 19 vaccine. The study aims to collect, analyze and summarize relevant findings in the literature scientifically, it is possible to be able to provide an assessment of what has been revealed by research so far about how social media (its content or its consumer use) can affect people’s knowledge and beliefs about the COVID-19 vaccine. Methods: Systematic review using Pubmed, ProQuest, Google Scholar and Science Direct. Result: 10 articles related to COVID 19 vaccine doubts on social media. Conclusion: Misinformation on the COVID 19 vaccine can endanger public opinion that is not anti-vaccine. For example, there are hoax news about the side effects of the COVID 19 vaccine that are not based on existing facts. In addition, the comments of people who are anti vaccine can influence public opinion, giving rise to doubts. Responding to the issue of COVID 19 vaccine hesitancy on social media such as Facebook, Twitter, and other social media. There has been a lot of misinformation related to the COVID-19 vaccine. Whereas social media platforms have the opportunity to provide information that can increase the use of the COVID-19 vaccine. Keywords: potential opinion, social media, hesitency, COVID 19